Influence of malting on the composition of millet (Pennisetum typhoideum) grains and the growth of Rhodotorula rubra and Torulopsis candida - A. A. Aliero, H. Shehu (Journal of Phytology, 2009)
A comparative study on the influence of malting on the composition of Pennisetum typhoideum grains and the growth of Rhodotorula rubra and Torulopsis candida was investigated. Result of proximate analysis indicated high crude protein content of 11.04% in three day malted grains (3DMG) which decreased with decrease in malting period. The contents of sodium, potassium, manganese and iron were equally higher in 3DMG. The unmalted grains had high ascorbic acid content of 7.50 mg/g which decreased markedly to 5.00 mg/g in all the malted grains. The cellular masses attained after culturing the yeast for 15 days was insignificant (P> 0.05). The biomass of R. rubra and T. candida in 3DMG was 369 and 357 mg respectively. Comparatively, the biomass obtained in yeast dextrose peptone media (YDPM) was comparatively lower with 367 and 349 mg in R. rubra and T. candida. The result of this study suggest that malted P. typhoideum grains media could be used as an alternative medium for culturing R. rubra and T. candida in the laboratory against conventional expensive YDPM and 3DMG proved to be promising.